Management of primary neoplasms of the appendix - Shen-Lin Wang; Ming-Jui Yang; Chin-Tsung Ting; Po-Chun Chen (Formosan Journal of Surgery, 2017)
Primary appendiceal adenocarcinoma is a rare disease, constituting < 0.5% of all neoplasms of the gastrointestinal origin. Primary appendiceal adenocarcinoma presents classically as an inflammatory condition such as acute appendicitis, and its preoperative diagnosis is difficult. In this case series, we report the cases of five patients with appendiceal neoplasms who underwent laparoscopic resection of appendiceal tumors and have thus far been healthy without any evidence of recurrence. Opinions regarding the most appropriate management of appendiceal tumors are variable. Recently, laparoscopic resection of appendiceal tumors has been added as a surgical option. If adequate preoperative assessment and definite diagnosis can be performed, laparoscopic resection of appendiceal tumors might become a feasible surgical option instead of open surgery in selected patients.